2021
DOI: 10.1002/jbm.a.37204
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin grafting to enhance skin sealing around transcutaneous titanium implant

Abstract: Intraosseous transcutaneous amputation prosthesis is a new approach in orthopedic implants that overcomes socket prosthesis problems. Its long‐term performance requires a tight skin‐implant seal to prevent infections. In this study, fibronectin (Fn), a widely used adhesion protein, was adsorbed or grafted onto titanium alloy. Fn grafting was performed using two different linking arms, dopamine/glutaric anhydride or phosphonate. The characterization of Fn‐modified surfaces showed that Fn grating via phosphonate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Various efforts at sealing the skin to the implant have not proven successful in long-term situations: Hall's aforementioned velour techniques along with various direct skin-to-metal efforts, textured or porous surfaces on cobalt-chrome [ 114 ] and titanium implants [ 115 ], and very recently adhesion protein surface modifications have been designed [ 116 ]. Can constructs that fix a static device (an osseointegrated implant) with a migratory tissue (basal skin maturation patterns) not lead to the skin either pulling the implant out or experiencing microtears which lead to inflammation and infection?…”
Section: Resultsmentioning
confidence: 99%
“…Various efforts at sealing the skin to the implant have not proven successful in long-term situations: Hall's aforementioned velour techniques along with various direct skin-to-metal efforts, textured or porous surfaces on cobalt-chrome [ 114 ] and titanium implants [ 115 ], and very recently adhesion protein surface modifications have been designed [ 116 ]. Can constructs that fix a static device (an osseointegrated implant) with a migratory tissue (basal skin maturation patterns) not lead to the skin either pulling the implant out or experiencing microtears which lead to inflammation and infection?…”
Section: Resultsmentioning
confidence: 99%
“…In the last decades, there has been increasing interest in the functionalization of surfaces with Fn, by direct adsorption or grafting on different surfaces, to enhance cell adhesion, proliferation, and spreading ( Toworfe et al, 2004 ; Middleton et al, 2007 ; Daum et al, 2020 ). In particular, Ghadhab et al (2021) showed that Ti surfaces functionalized with covalently grafted Fn enhance dermal fibroblast adhesion, spreading, and proliferation and that the adhesion strength between the functionalized material and a bioengineered dermal tissue is higher ( Ghadhab et al, 2021 ). Recently, studies focused on the use of Fn in combination with other molecules in order to create 3D biomimetic environments to enhance cell attachment ( Ngankam et al, 2004 ; Zanina et al, 2011 ) and cytocompatibility for tissue engineering ( Ravi et al, 2013 ; Mauquoy and Dupont-Gillain 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alternative strategies aim to enhance soft-tissue sealing around the implant and thus reduce bacterial invasions and related infection. This includes modifications of the topography—roughness, porosity, and nanostructuration (grooves, nanotubes)—that increases the surface area and thus the surface available for soft tissue attachment ( Zitzmann et al, 2002 ; Puckett et al, 2010 ; Atsuta et al, 2014 ); modification of surface chemistry increasing surface hydrophilicity ( Kloss et al, 2011 ; Abdallah et al, 2017 ); and grafting of biomolecules like proteins fibronectin (Fn) or laminin ( Oyane et al, 2011 ; Ghadhab et al, 2021 ) and adhesion peptides like RGD or laminin-derived peptides ( Bellis 2011 ; Fischer et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…[46] PVA Enhancing optimal migratory behavior in human hepatocytes [47] GA cross-linking Plasma-treated silica and polytetrafluoroethylene (PTFE) Increasing CBD accessibility and bovine aortic endothelial cell adhesion [48,49] Modification with phosphonate Titanium Increasing dermal fibroblast adhesion, spreading, and proliferation; enhancing the strength of adhesion to bioengineered dermal tissue [50] One of the first approaches to Fn-covalent immobilization was reported by Kobayashi and Ikacia on polyvinyl alcohol (PVA) hydrogels for contact lens applications [29]. In this case, PVA, known to be a highly bio-inactive polymer, was modified by the addition of isocyanate groups able to react with the amino and hydroxyl groups of Fn to form urea and urethane bonds, respectively [29].…”
Section: ] Fibrinogenmentioning
confidence: 99%
“…A recent study showed that the hydrophilic/hydrophobic nature of the linker, its length, and the binding site on the protein influenced the Fn conformation and RGD accessibility [51]. Fn grafting has also been used to functionalize titanium surfaces in the context of transcutaneous implants to enhance soft-tissue sealing around the implant [50]. In this study, the authors showed that Fn grafted via phosphonate-linking arms increases dermal fibroblast adhesion, spreading and proliferation, and the strength of the adhesion between the functionalized material and the bioengineered dermal tissue.…”
Section: ] Fibrinogenmentioning
confidence: 99%